(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
This paper examines the policy initiatives, taken since the 1970s, that have shaped the development of education in Pakistan, and other primary issues related to it. The paper reviews governmental policy documents alongside an analysis of the available relevant data on corresponding issues. This examination illuminates competing interests and factors that have made the goal of quality universal public education in Pakistan elusive. Specifically, this study reveals that the quest for universal education has been stymied by interconnected, often self-perpetuating factors, such as:- unprecedented population growth alongside increasing gender disparities, inadequate funding coupled with systemic corruption, diminished democratic aims in education and the increasing influence of religious zealotry. The paper concludes by suggesting that education in Pakistan must become a matter of common interest.